Experimental Study on Thermal Behaviour of Double Pipe Helical Flow Heat Exchanger. Issue 1 (February 2020) - Karthikeyan, R; Thangavel, P; Naveen, R; Selvakumar, P; Astra, S
Abstract: The warmth among the fluids is transferred by a tool named warmth exchanger. Now a days, various types of heat exchangers existed with different configurations, in each configuration different types of flow of fluids are followed. In this paper single helical tube made of copper is arranged inside the shell like structure and helical baffle. Double pipe helical flow warmth exchanger which is used to transfer warmth or otherwise known as heat is considered as main configuration. The main advantage of the pipe-in-pipe helical flow is more contact on uppermost area for transferring heat as compared with the everyday based pipe-in-pipe exchanger. The performance of this model is analyzed with water in both inlets in same directions and then opposite directions. The inlet, outlet temperatures and flow costs of the both fluids are measured. From the acquired effects, the effectiveness of double helical drift warmth exchanger is sort of 20% extra than the normal double pipe warmness exchanger and it gives warm water output temperature almost 4°C lower than the regular warmthexchanger.